Status of pollinators and pollination services in the Eastern Indian agricultural landscape (Webinar session 3) - Basu, Parthiba (International Maize and Wheat Improvement Center, 2023)
The TAFSSA CGIAR Initiative is hosting a series of webinars to highlight research from South Asia on food security, sustainable healthy diets, farmer livelihoods and resilience, and land, air, and groundwater conservation. For the third webinar on February 28, Dr. Parthiba Basu will present. Dr. Parthiba Basu has a Ph.D. in Ecology and is a Professor at the Department of Zoology, University of Calcutta. He heads the Centre for Agroecology and Pollination Studies founded in 2012 at University of Calcutta. His research interest is biodiversity and ecosystem functioning along ecological gradients- particularly in the agricultural landscape. A major research focus has been the diversity of pollinators and their ecosystem service delivery in agro-ecosystems.